Faint early-type stars in the neighbourhood of the H II region RCW 38 - Muzzio, Juan Carlos (1979)
We used UBV photographic photometry to search for faint early-type stars in a region of about 1200arcmin2 in the neighbourhood of the Hn region RCW 38. The limiting magnitude of the search is K= 15.49, 16.43 and U= 16.83 mag. Fifteen new early-type stars were found and most of them are probably related to the H ii region.